Resource allocation in wireless networks with RF energy harvesting and transfer - Lu, Xiao (2018)
RF energy harvesting and transfer techniques have recently become alternative methods to power the next generation of wireless networks. As this emerging technology enables proactive replenishment of wireless devices, it is advantageous in supporting applications with QoS requirements. This article focuses on the resource allocation issues in wireless networks with RF energy harvesting capability, referred to as RF-energy harvesting networks (RF-EHNs). First we present an overview of the RF-EHNs, followed by a review of a variety of issues regarding resource allocation. Then we present a case study of designing in the receiver operation policy, which is of paramount importance in RF-EHNs. We focus on QoS support and service differentiation, which have not been addressed in previous literature. We also outline open research directions.